Emergent Investigations in Design Practice: Lessons from Engaging the Social Sciences Undergraduates in Design-based Concept Learning - Khunyakari, Ritesh (Voices of Teachers and Teacher Educators, 2022)
This paper reports the findings from an engagement of social sciences undergraduates in design thinking, which encouraged them to identify relevant conceptual ideas in life sciences that can be applied for societal welfare. About 12 groups of 4 to 6 undergraduates (participants)worked collaboratively on a design task around an idea identified and owned by the group itself. A case study approach enabled close follow-upon the group’s work by analysing their visual and written productions, and prototype outcomes. Evidence from two cases is used to exemplify design-based concept learning and understand how the experience of designing necessitated emergent investigations. The design thinking process afforded close attention to structure-function relationships, deepened an understanding of concepts, conscious understanding of material properties and assemblies, and building empathetic perspectives for appreciation of natural design and human-designed technologies. The emergent investigations undertaken by a group during the various phases of designing suggests its critical role in systematically evaluating formative design ideas, supporting iterative reflexivity through an interplay of materials, sketches and models that afforded conceptual transitions.